SISTEM PENDIDIKAN NASIONAL DAN PENDIDIKAN ISLAM - Muthoifin, Muthoifin (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2015)
AbstractThee focus of this research is the pro" le of Ki Hadjar Dewantara, his educational thought based on the perspective of Islamic education review, the research is focused on the aspects of the conception of education issues, including: basic, content and education systems. The research method used is the libraries research. By approaching to the history and biography of Ki Hadjar.While the data collection consists of primary and secondary data sources. Techniques of data analysis was using content analysis, descriptive, comparative and inductive. The results of the study. 1, the concept of education Ki Hadjar focused on aspects of guidance to children in order to achieve happiness based on the nature of nature. ! is is not consistent with the concept of Islamiceducation that focused on aspects of worship and Tawheed based on divine revelation. 2, Ki Hadjar’s basic education is the principle Pancadarma, which of the " ve principle is explicitly no principle of divinity, it is contrary to basic Islamic education which is based on al-Quran and al-Sunnah. 3) Ki Hadjar’s education system, good goals, curriculum, methods, teachers, students and the evaluation does not lead and is tied to the value of faith and worship, it is also not in line with the Islamic education system has always associate with both religious values .Keywords: Education system, Ki Hadjar Dewantara, Islamic education